Irrigation levels and use of hydro retainer polymer in greenhouse lettuce production - Welcio R. da Silva; Leandro C. Salomão; Débora R. M. Pereira; Henrique F. E. de Oliveira; Alexandre I. de A. Pereira; Fernando S. Cantuario (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT One of the potential alternatives to improve the use of water resources is the use of hydro retainer polymer applied to the soil. The objective of this study was to evaluate how irrigation levels and doses of hydro retainer polymer interfere in the production of ’Vanda’ lettuce. The experiment was carried out from December 2017 to January 2018 under protected environment in the Instituto Federal Goiano, Urutaí Campus, Goiás State, GO, Brazil (17º 29’ 10” S of latitude, 48º 12’ 38” W of longitude and 697 m of altitude). The work tested four irrigation levels of 50, 75, 100 and 125% of the evaporation obtained daily by the hook micrometer and five doses of hydrogel polymer (0, 50, 100, 150 and 200 g plant-1). The experimental design was a randomized block design in a scheme of split-plot and four blocks. Canopy fresh and dry mass, plant height, number of leaves and productivity were evaluated. There was 29.24% increase in the dry mass comparing the hydro retainer polymer doses of 0 and 169.28 g and an increase of 14.36% of the height of plants when compared with the irrigation levels of 50 and 125%. The use of a hydro retainer polymer provided a significant increase in all the evaluated productive variables. The irrigation levels influence the fresh mass from aerial part, plant height and productivity. The productivity increased 18.42% for the irrigation levels used and the highest estimated values were presented in the dose of 157.49 g (14.46 t ha-1) hydro retainer polymer.